PENINGKATAN KEMAMPUAN BERPIKIR KRITIS SISWA SMP MELALUI MODEL TEAM BASED LEARNING - Rizka, Shinta Lailatul; Nurita, Tutut (PENSA: E-JURNAL PENDIDIKAN SAINS, 2023)
This study aimed to describe the improvement of junior high school students critical thinking skills in sound material using models Team Based Learning. The type of research used is quantitative research with the method pre-experimental with a plan one group pretest-posttest. The subject of this research involved 30 students. The data collection technique used was the written test method in the form of six essay questions. The data analysis technique used is test n-gain score and the data obtained were analyzed in a quantitative descriptive manner. The results showed that students critical thinking skills in sound material used Team Based Learning experienced an increase in the overall average indicators n-gain score 0.6 with moderate improvement criteria. In order to better improve the model can be done Team Based Learning repeatedly so that students critical thinking skills increase.